Increased arterial stiffness gradient in badminton players with dominant unilateral arm movements is different from the increase in arterial stiffness gradient with advancing age - Kim, D. Y.; Lee, R.; Hwang, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Pulse wave velocity (PWV), a validated measure of arterial stiffness, is a clinical indicator for cardiovascular disease risk. Arterial stiffness gradient, a novel marker of cardiovascular morbidity and mortality, is the ratio of central (aortic or carotid to femoral, cf) PWV to peripheral (arm or leg) PWV. Increased central arterial stiffness is a negative feature seen in the aged vasculatures. Regular physical activity reduces central arterial stiffness in various populations including the aged adults and chronic disease patients. But its effect on peripheral PWV is still controversial. In addition, to date, few studies have investigated changes in peripheral PWV in response to unilateral exercise, and no studies have investigated changes in arterial stiffness gradient. Therefore, the purpose of this study was to compare the differences in arterial stiffness gradient as well as to analyze the difference in armPWV between both arms according to the degree of unilateral arm exercise participation. METHODS: Twenty-six young women participated in this study; eight elite-level badminton players (ELIT), ten club-level badminton players (CLUB), and eight age-matched sedentary participants (CONT). Central blood pressure and carotid-femoral PWV (cfPWV) as the central artery stiffness were measured using SphygmoCor Xcel system. Brachial-radial PWV (armPWV) as the peripheral stiffness was measured using Doppler Flowmeters and the associated data was collected and analyzed by PowerLab data acquisition system including Labchart Pro V8 software. Arterial stiffness gradient was calculated as the ratio of cfPWV to armPWV at both dominant and non-dominant arm, respectively. Body composition was assessed by using a segmental bioelectrical impedance analyzer. RESULTS: In the dominant arm, the arterial stiffness gradient of ELIT and CLUB were significantly higher than CONT (0.73 vs. 0.46, ELIT vs. CONT, PP<0.001; 0.59 vs. 0.46, CLUB vs. CONT, P=0.04). The arterial stiffness gradient of ELIT was also significantly higher than CLUB (0.73 vs. 0.59, ELIT vs. CLUB, P=0.03). In the non-dominant arm, the arterial stiffness gradient of ELIT was significantly higher than CONT (ELIT: 0.59 vs. CON: 0.44 P= 0.01), but there was no significant difference between ELIT and CLUB, and CLUB and CONT (0.59 vs. 0.53, ELIT vs. CLUB, P=0.36; 0.53 vs. 0.44, CLUB vs. CONT, P=0.09). The dominant and non-dominant armPWV were positively correlated with cfPWV and central blood pressures (r=0.41, P=0.04). The dominant and non-dominant armPWV were also inversely associated with the dominant arm muscle mass and whole-body muscle mass (r=-0.49, P=0.01). CONCLUSION: The more unilateral exercise accumulated in the dominant arm, the higher the arterial stiffness gradient. Since the increased arterial stiffness gradient in active young adults is caused by decreased armPWV rather than increased cfPWV, an increase in arterial stiffness gradient may be associated with a reduced cardiovascular disease risk in the future.